Predictors of Shoulder Pain in Manual Wheelchair Users - Walford, Shelby L. (Clin Biomech (Bristol, Avon), 2019)
BACKGROUND: Manual wheelchair users rely on their upper limbs to provide independent mobility, which leads to high muscular demand on their upper extremities and often results in shoulder pain and injury. However, the specific causes of shoulder pain are unknown. Previous work has shown that decreased shoulder muscle strength is predictive of shoulder pain onset, and others have analyzed joint kinematics and kinetics, propulsion technique and intra-individual variability for their relation to shoulder pathology. The purpose of this study was to determine in a longitudinal setting whether there are specific biomechanical measures that predict shoulder pain development in manual wheelchair users. METHODS: All participants were asymptomatic for shoulder pain and categorized into pain and no pain groups based on assessments at 18 and 36 months later. Shoulder strength, handrim and joint kinetics, kinematics, spatiotemporal measures, intra-individual standard deviations and coefficients of variation were evaluated as predictors of shoulder pain. FINDINGS: Individuals who developed shoulder pain had weaker shoulder adductors muscles, higher positive shoulder joint work during recovery, and less trunk flexion than those who did not develop pain. In addition, relative intra-individual variability was a better predictor of shoulder pain than absolute variability, however future work is needed to determine when increased versus decreased variability is more favorable for preventing shoulder pain. INTERPRETATION: These predictors may provide insight into how to improve rehabilitation training and outcomes for manual wheelchair users and ultimately decrease their likelihood of developing shoulder pain and injuries.